2021
DOI: 10.1101/2021.07.15.452450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fatty Alcohols, a Minor Component of the Tree Tobacco Surface Wax, Reduce Insect Herbivory

Abstract: Despite decades of research resulting in a comprehensive understanding of epicuticular wax biosynthesis and metabolism, the function of these almost ubiquitous metabolites in plant-herbivore interactions remains unresolved. To develop a better understanding of this role, we investigated plant-herbivore interactions in four Nicotiana glauca (tree tobacco) genome edited mutants. This included [eceriferum1 (cer1), eceriferum3 (cer3), beta-ketoacyl-coA synthase6 (kcs6), and fatty acyl-coA reductase (far)] displayi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…Although enhanced herbivore resistance has been reported in other plant species (Way and Murdie, 1965; Mori, 1982; Negin et al, 2021, 2023), our study is the first to show a consistent trade‐off between wax production and herbivore‐induced JA biosynthesis in maize (Figures 4, 5). Connections between lipid fluxes for wax and JA biosynthesis were previously suggested in cotton ( Gossypium hirsutum ) and orange ( Citrus × sinensis ) plants.…”
Section: Discussionsupporting
confidence: 53%
“…Although enhanced herbivore resistance has been reported in other plant species (Way and Murdie, 1965; Mori, 1982; Negin et al, 2021, 2023), our study is the first to show a consistent trade‐off between wax production and herbivore‐induced JA biosynthesis in maize (Figures 4, 5). Connections between lipid fluxes for wax and JA biosynthesis were previously suggested in cotton ( Gossypium hirsutum ) and orange ( Citrus × sinensis ) plants.…”
Section: Discussionsupporting
confidence: 53%
“…Toxins in the leaf wax may contribute to this inhibitory effect (Belete, 2018). For instance, Negin et al (2021) found that fatty alcohols in the epicuticular waxes of Nicotiana glauca (Solanaceae) tend to reduce caterpillar growth. In our experiment, mass gain was lower in caterpillars placed on S.…”
Section: Discussionmentioning
confidence: 99%
“…After 11 days, survival was scored, and live caterpillars were weighed. This timeframe was chosen following a previous trial with Nicotiana glauca in which S. exigua larvae were confined on leaves for a similar duration (Negin et al ., 2024). Four-day-old C. virescens larvae hatched on beet armyworm diet were weighed, and those weighing 5-12 mg were placed in organza mesh bags on individual N. benthamiana leaves, with a single caterpillar in each bag.…”
Section: Methodsmentioning
confidence: 99%